Therapeutic potential of mesenchymal stem cells for refractory inflammatory and immune skin diseases - Chunting Hua; Siji Chen; Hao Cheng (Taylor & Francis Group, 2022)
Inflammatory and immunological skin diseases such as psoriasis, systemic sclerosis, dermatomyositis and atopic dermatitis, whose abnormal skin manifestations not only affected life quality but also caused social discrimination, have been wildly concerned. Complex variables such as hereditary predisposition, racial differences, age and gender can influence the prevalence and therapeutic options. The population of patients with unsatisfactory curative effects under current therapies is growing, it's advisable to seek novel and advanced therapies that are less likely to cause systemic damage. Mesenchymal stem cells (MSCs) have been proven with therapeutic benefits in tissue regeneration, self-renewal and differentiation abilities when treating refractory skin disorders in preclinical and clinical studies. Here we highlighted the immune modulation and inflammation suppression of MSCs in skin diseases, summarized current studies, research progress and related clinical trials, hoping to strengthen the confidence of promising MSCs therapy in future clinical application.